EWIGE 2 – Update and Extension of the EUROMOD Wealth Taxation Project - Jonas Boone; Johannes Derboven; Sarah Kuypers; Francesco Figari; Gerlinde Verbist (European Commission, Joint Research Centre (JRC), 2019)
Taxing wealth has received increased attention in both the academic and political debate, as a way to reduce inequality of both income and wealth. However, analytical tools are still underdeveloped when it comes to empirical analyses of different types of wealth-related taxes and policies. New household surveys as those developed as part of the Eurosystem Household Finance and Consumption Survey (HFCS) represent a milestone for this purpose. Yet, distributional analysis of income and wealth requires information on disposable income and wealth which are not available, as the new Eurosystem data includes only gross income values. Moreover, in order to simulate the effects of wealth taxes and (budget neutral) reforms to the current direct taxes a microsimulation model such as EUROMOD is needed. Integrating the HFCS data in EUROMOD makes it possible to assess the effect of different current and hypothetical wealth taxes and policies on the distribution of income and wealth. In this report we build further on a pilot study (see Kuypers et al., 2017), in which the HFCS data have been converted into a EUROMOD database for six countries that were part of the first wave of the HFCS. More specifically, the HFCS-EUROMOD combination is applied for the second wave of the HFCS data and the scope has been broadened to 17 EU countries (6 original from the pilot study and 11 new ones). We discuss the process of how the HFCS data have been transformed to fit the EUROMOD context, how the simulation of wealth taxes and policies has been added to the EUROMOD country files and we assess how the simulation results compare with other available sources. Finally, we also briefly discuss an example of a simulation that can be performed by using the new tool.
Keywords: 330; Wealth taxation; EUROMOD; HFCS